Pengaruh Customer Value, Kualitas Layanan, dan Persepsi Harga Terhadap Pembelian Ulang di Super Dazzle Gejayan - Rosy Tabita; Audita Nuvriasari (Jurnal Perilaku dan Strategi Bisnis, 2025)
This study aims to analyze the effect of Customer Value, Service Quality, and Price Perception on Re-Purchasing at Super Dazzle Gejayan. This research uses an explanatory research type with a quantitative approach. The sampling technique employed is nonprobability sampling, with a total sample of 100 respondents who have shopped at Super Dazzle Gejayan. Data were collected using a questionnaire. Data analysis was conducted using descriptive analysis and inferential analysis with multiple linear regression methods. The results of this study indicate that: (1) Customer Value has a significant positive effect on Re-Purchasing, (2) Service Quality has a significant positive effect on Re-Purchasing, (3) Price Perception has no significant effect on Re-Purchasing